2020
DOI: 10.1186/s41983-020-00172-5
|View full text |Cite
|
Sign up to set email alerts
|

A study of diffusion tensor imaging of median nerve in diabetic peripheral neuropathy

Abstract: Objective: To evaluate the role of diffusion tensor imaging (DTI) in the evaluation of diabetic peripheral neuropathy (DPN) compared to clinical scores and nerve conduction studies (NCS). Patients and methods: We included 30 patients with diabetes mellitus complaining of neuropathy symptoms and 15 healthy volunteers. All subjects underwent evaluation using 1.5-T DTI of median nerves and NCS. Patients underwent clinical evaluation using the Neuropathy Deficit Score (NDS), Neuropathy Impairment Score in the Lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Question 2 asks whether the populations studied were clearly defined. Many of the earlier studies did not distinguish between type 1 and 2 diabetes, and often did not make clear from the methods section the number of patients from each group, or which patients were on insulin treatment (Koechner et al, 1995 ; Shibata et al, 1998 ; Wu et al, 2017 ; Edward et al, 2020 ) (14/18 complied). Question 8 asks whether different “levels” of exposure where compared, which in this context relates to whether groups were stratified based on severity or duration of neuropathy or diabetes, to make a more convincing link between disease and MR biomarkers (9/18 complied).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Question 2 asks whether the populations studied were clearly defined. Many of the earlier studies did not distinguish between type 1 and 2 diabetes, and often did not make clear from the methods section the number of patients from each group, or which patients were on insulin treatment (Koechner et al, 1995 ; Shibata et al, 1998 ; Wu et al, 2017 ; Edward et al, 2020 ) (14/18 complied). Question 8 asks whether different “levels” of exposure where compared, which in this context relates to whether groups were stratified based on severity or duration of neuropathy or diabetes, to make a more convincing link between disease and MR biomarkers (9/18 complied).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have consistently shown a reduction in FA in patients with DPN compared with both healthy controls and diabetic patients without DPN, for the sciatic nerve (Vaeggemose et al, 2017a , b ; Vaeggemose et al, 2020 ), tibial nerve (Vaeggemose et al, 2017a , b ; Wu et al, 2017 ; Vaeggemose et al, 2020 ; Jende et al, 2020a ), and common peroneal nerve (Wu et al, 2017 ), which has been demonstrated at the thigh and ankle level. Edward et al ( 2020 ) also demonstrated reduced FA in the distal median nerve in the wrist. ADC or MD is a measure of the average diffusivity of protons across all directions, with higher values in nerves suggesting some degree of axonal disruption (Tievsky et al, 1999 ).…”
Section: Narrative Reviewmentioning
confidence: 92%
“…Ten studies (32%) were performed at a eld strength of 1•5 tesla 17,29,32,35,38,42,44,49,50,52 , twenty one (65%) at 3 tesla 16,19,[26][27][28]30,31,33,34,36,37,[39][40][41]43,[45][46][47][48]51,53 , and one at 7 tesla 18 . The median echo and repetition times were 87ms (IQR 65-91, range 21-103) and 7000ms (IQR 3800-7650, range 1470-10,254), respectively.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The FA of the median nerve in asymptomatic adults was reported in 29 studies [16][17][18][19][26][27][28][29][30][31][32][33][34][35][37][38][39][40][41][43][44][45][46][47][48][49][50][51]53 .…”
Section: Evidence Synthesis: Asymptomatic Adultsmentioning
confidence: 99%
See 1 more Smart Citation